Improving productive performance and mitigating harmful emissions from laying hen excreta via feeding on graded levels of corn DDGS with or without Bacillus subtilis probiotic. Issue 5 (17th May 2016) - Abd El‐Hack, M. E.; Mahgoub, S. A.; Alagawany, M.; Ashour, E. A.
Summary: An experiment that included some inclusions of corn distillers dried grains with solubles (DDGS) with or without supplementation of probiotic bacteria to Hi‐sex Brown laying hen diets was conducted to evaluate the impacts on performance, egg quality, blood metabolites and nitrogen and phosphorus excretion in the manure. A total of 216 twenty‐two‐week‐old Hi‐sex Brown laying hens were randomly divided into eight treatment groups in a factorial design (4 × 2) experiment, which included four levels of DDGS (0, 50, 100 and 150 g/kg diet) plus two levels of Bacillus subtilis probiotic (0 or 1000 mg/kg diet, with a concentration of 1.5 × 108 CFU/g of dried product). The experimental period extended from 22 to 34 weeks of age. The results showed that linear increase in DDGS level up to 150 g/kg improved (p ≤ 0.01) the values of feed consumption, egg shape index and yolk colour compared to the control and other treatment groups. Inclusion of dietary DDGS up to 150 g/kg in layer diets led to a significant decrease in egg mass and a significant increase in Haugh unit score compared to other groups. In the bacillus group, the values of feed conversion, egg weight and egg mass enhanced by 6.45, 3.27 and 7.60% respectively compared with the control diet. Total protein, albumin, triglycerides, cholesterol, calcium and ammonia in serum were significantly (p ≤ 0.01) influenced by DDGS inclusion. The excreted nitrogen decreased by 8.62 and 4.31% in hens fed 50 or 100 g/kg of DDGS respectively, while excreted phosphorous decreased by 3.33, 7.22 and 10.56% in hens fed 50, 100 or 150 g/kg of DDGS respectively as compared to the control group. It could be concluded that increasing DDGS inclusion level in the diet up to 10% and the supplementation of probiotic bacteria improved the productive performance of laying hens and mitigated the harmful emissions from chicken manure; this means better production within environmentally friendly conditions.